STRATEGI GURU DALAM MENCIPTAKAN LINGKUNGAN BELAJAR INKLUSIF BAGI SISWA YANG TERINDIKASI AUTIS DI SEKOLAH DASAR - Ardianzah, Erwin; Joko Setiono; Choiriyah Widyasari; Minsih, Minsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Inclusive education has become an urgent necessity to ensure that students identified with autism receive equal learning opportunities. This study aims to explore teachers’ strategies in creating an inclusive learning environment for students identified with autism in Grade 1 at SDN 02 Jenawi. The research employed a descriptive qualitative approach with data obtained from classroom teacher interviews, observations of student behavior, and documentation of learning activities. Data collection techniques included in-depth interviews, participatory observation, and document analysis related to inclusive learning. Data validity was ensured through source and technique triangulation by comparing interview, observation, and documentation findings. Data analysis was conducted interactively using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results indicate that teachers implemented differentiated instruction, positive reinforcement, regular monitoring, and collaboration with parents and peers, which effectively enhanced student participation, social skills, and independence. These findings contribute to inclusive education practices at the elementary school level and serve as a reference for teachers in designing adaptive learning strategies responsive to individual student needs.